2016
DOI: 10.1089/end.2015.0723
|View full text |Cite
|
Sign up to set email alerts
|

The Simbla TURBT Simulator in Urological Residency Training: From Needs Analysis to Validation

Abstract: The Simbla TURBT simulator is a valid, feasible, and acceptable educational tool for training procedural skills and may be implemented in the urological curriculum to complement learning in clinical practice. TNA is valuable in defining training objectives and evaluating the educational value of a simulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In a face validity study of the dVT robotic surgery simulator, experts rated the simulator as less useful for training experts than for students/juniors and pointed out to the experts’ need for more critical and advanced procedures in gynaecological surgery and that simulators specifically designed for learning basic skills are less preferable to experts [ 32 ]. Creating simulated scenarios to correspond to real ones is always a challenge [ 3 , 29 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a face validity study of the dVT robotic surgery simulator, experts rated the simulator as less useful for training experts than for students/juniors and pointed out to the experts’ need for more critical and advanced procedures in gynaecological surgery and that simulators specifically designed for learning basic skills are less preferable to experts [ 32 ]. Creating simulated scenarios to correspond to real ones is always a challenge [ 3 , 29 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al 22 utilised the Bristol TURBT Trainer (Limbs and Things) and also demonstrated face, content and construct B validity. Similarly, the Simbla TURBT Simulator was also evaluated by de Vries et al 23 and demonstrated face, content and construct B validity amongst 76 participants consisting of novices, intermediaries and experts. All three models received a LoR of 3.…”
Section: Transurethral Resection Of Bladder Tumours (Turbt)mentioning
confidence: 99%
“…A total of 76 residents and urologists with different levels of endoscopic experience were included. All participants received a standardized verbal introduction on the use of the validated Simbla TURBT simulator [21] from one of the tutors (HvG or HdV). Subsequently, each participant performed two standardized TURBT procedures.…”
Section: Study Design and Participantsmentioning
confidence: 99%